Determinan Nilai Tukar Petani Perkebunan Rakyat Di Indonesia - Nugrahaning Widi, Mohamad Aniful Izza (Efficient: Indonesian Journal of Development Economics, 2021)
This study aims to identify the factors that influence the smallholder estate farmer's terms of trade (FTT) in Indonesia. The time period that used in this study was from 2014 to 2018. The variables used are smallholder estate production, inflation price of estate product, wage of farm laborers, and distribution of subsidized fertilizer. The type of data used in this study is secondary data. The technique of collecting data is by literature review or documentation method. The population used was 32 provinces in Indonesia. The method used is panel data regression analysis, the model of regression that used is Fixed Effects Model (FEM). The model was chosen based on the Chow Test and the Hausman Test. The results of this study indicate that the smallholder estate production and inflation price of estate product have a positive significant effects to the smallholder estate FTT in Indonesia. Wage of farm laborers have a negative significant effect on the smallholder estate FTT in Indonesia. Whereas the distribution of subsidized fertilizer have no significant effect to the smallholder estate FTT in Indonesia. Penelitian ini bertujuan untuk mengidentifikasi faktor – faktor yang mempengaruhi nilai tukar petani (NTP) perkebunan rakyat di Indonesia. Periode waktu tahun penelitian ini adalah tahun 2014 hingga tahun 2018. Variabel yang digunakan adalah produksi perkebunan rakyat, inflasi harga produk perkebunan, upah buruh tani, dan tingkat realisasi penyaluran pupuk bersubsidi. Jenis data yang digunakan dalam penelitian ini merupakan data sekunder. Teknik pengumpulan data menggunakan studi pustaka. Populasi yang digunakan adalah 32 provinsi di Indonesia. Metode analisis yang digunakan adalah regresi data panel. Adapun model yang terpilih adalah fixed effects model (FEM). Model dipilih berdasarkan uji chow dan uji hausman. Hasil penelitian menunjukkan bahwa variabel produksi perkebunan rakyat dan inflasi harga produk perkebunan berpengaruh positif signifikan terhadap NTP perkebunan rakyat di Indonesia. Upah buruh tani berpengaruh negatif signifikan terhadap NTP perkebunan rakyat di Indonesia. Sedangkan tingkat realisasi penyaluran pupuk bersubsidi tidak berpengaruh signifikan terhadap NTP perkebunan rakyat di Indonesia.